Unity through diversity - Abdul Aziz Sachedina (International Institute of Islamic Thought, 1988)
Islam: Faith, Submission and Action Islam emerged as a moral challenge to humanity to respond to the call of the faith and create an ethically just public order that would reflect the ‘active submission’ (the term, Islam signifies this sense) to the Divine Will. Accordingly, creation of the just public order was viewed as the direct consequence of faith in the Islamic revelation where mere profession of faith without moral and religious commitment to create an Islamic order was considered hypocritical. In fact, the Qur’an views faith ('Iman) as generating moral social behavior which ought to be translated in the creation of a morally just order on earth. Consequently, the term Islam should never be defined as mere ‘submission’ without the understanding that the necessary consequence of that ‘submission’ results in the transformance of the individual into a ‘righteous’ person, and the society into an ideal public order. The Qur’an, however, also took note of the weaknesses in human nature and prescribed solutions for humanity to rise above these mostly self-cultivated weaknesses when confronted by ‘glitterings’ of the worldly, material life. The Qur’anic prescription consisted of creating a system whereby humanity, having responded to the Divine call, was thus held responsible in two areas of its relationship. First, in the area of its relationship to Allah (SWT) by virtue of being created by Him; and, second, in the area of interpersonal relationship by virtue of its composition of individual human beings. In the first area, where religious prescriptions directed the human life towards an existence of devotion and commitment, the purpose of Divine guidance was to endow humanity with volition and cognition to realize the necessity of showing gratitude to the Creator. It, therefore, proceeded with an exercise of choice, even when the faith was declared as a Divine gift. The reason was that humanity could not be held responsible for ignoring the call of the faith if there was compulsion involved in the initial offer of faith. After all, becoming a faithful person, according to the Qur‘an, is to ...